Orzecznicze poszerzanie granic równouprawnienia – przypadek praw socjalnych migrujących obywateli Unii Europejskiej - Cieśliński, Aleksander (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The idea behind this paper is to analyze the development of the European Court of Justice/Court of Justice of the European Union case law on the access to social rights by non-economic migrants in the host Member State. Without a doubt, this topic is particularly interesting and serves as a perfect example of providing subjective rights almost exclusively by way of a teleological interpretation of the principle of non-discrimination on the grounds of nationality rather than by statutory law. As one of the hallmarks of the EU legal system, which, nonetheless, is quite unusual for Polish lawyers, it deserves more serious consideration. To that end, first the idea of equal social treatment and the means of protecting the interests of national social systems are analyzed. The major emphasis, however, is put on describing the way the Court of Justice has managed to expand the limits of non-discrimination in specific rulings. Even if nowadays this development has become partly blocked, the very process appears to hold a more universal significance
Keywords: obywatelstwo Unii Europejskiej; prawa socjalne; swoboda przepływu osób; niedyskryminacja; równouprawnienie